2022
DOI: 10.7759/cureus.28218
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Methylenetetrahydrofolate Reductase (MTHFR) C677T Variation With Susceptibility of Patients With Ischemic Stroke: A Meta-Analysis

Abstract: Discovery and validation of genetic factors for multifactorial and polygenic disorders like stroke are needed to make progress in precision medicine. Although some traditional risk factors for stroke have been identified, they do not fully explain the pathophysiological mechanism of ischemic stroke. The research of genetic risk factors is becoming increasingly relevant in the understanding of stroke mechanisms and the finding of population-specific therapeutic targets. The methylenetetrahydrofolate reductase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
1
1
0
2
Order By: Relevance
“…The TT genotype is commonly linked with elevated Hcy levels through reduction in the activity of MTHFR (23). In the present study, Hcy level was significantly correlated with genotype (CT/TT) of the MTHFR C677T gene polymorphism among both the control and the CI groups, which was consistent with findings in Asian, Singaporean, Malaysian, Tunisian, Chinese, and Polish populations (24)(25)(26)(27)(28). However, studies of Indonesian, Zambian, and Brazilian populations have found no association between MTHFR C677T polymorphism and risk of CI (29-31).…”
Section: Genotype Nsupporting
confidence: 90%
“…The TT genotype is commonly linked with elevated Hcy levels through reduction in the activity of MTHFR (23). In the present study, Hcy level was significantly correlated with genotype (CT/TT) of the MTHFR C677T gene polymorphism among both the control and the CI groups, which was consistent with findings in Asian, Singaporean, Malaysian, Tunisian, Chinese, and Polish populations (24)(25)(26)(27)(28). However, studies of Indonesian, Zambian, and Brazilian populations have found no association between MTHFR C677T polymorphism and risk of CI (29-31).…”
Section: Genotype Nsupporting
confidence: 90%
“…Mutations in the MTHFR gene, which is involved in homocysteine metabolism, cause increased homocysteine (hcy) buildup in the circulation. As a result, a change in the function of the MTHFR pathway increases the risk of cerebrovascular illness 15 17 . To develop precision healthcare, genetic factors for complex and polygenic disorders like stroke must be identified and verified.…”
Section: Discussionmentioning
confidence: 99%
“…The two main methods for lowering serum Hcy levels are oral FA or 5-MTHF administration or intramuscular injections of FA. However, it should be emphasized that vitamins B12 and B6 are also essential cofactors in the process of metabolizing hydroxy citric acid, in addition to folate [ 46 , 47 ]. One of the two irreversible mechanisms-transsulfuration to cysteine or remethylation to methionine-can easily degrade Hcy because it can be found close to the center of metabolic processes (Fig.…”
Section: Methodsmentioning
confidence: 99%